Hubungan Antara Task-Approach Skills dengan Career Decision Making pada Siswa SMK - Fauziah, Nur Sifa; Saraswati, Sinta (Universitas Negeri Semarang, 2020)
Abstrak Tujuan penelitian yaitu mengetahui dan menganalisis hubungan antara aspek-aspek task-approach skills dengan aspek-aspek career decision making siswa. Pendekatan penelitian adalah kuantitatif korelasional dengan 142 sampel dari 240 siswa, diambil menggunakan simple random sampling. Analisis yang digunakan adalah deskriptif kuantitatif dan uji hipotesis korelasi Pearson Product Moment. Hasil analisis deskriptif kuantitatif menunjukan tingkat task-approach skills dan career decision making termasuk dalam kategori sedang. Hasil analisis stiatistik inferensial menunjukan ada hubungan positif dan signifikan antara task-approach skills aspek standar dan nilai kinerja dengan rational career decision making (r=0,145; p=<0,05). Ada hubungan negatif antara task-approach skills aspek proses persepsi dan kognitif dengan impulsive career decision making(r=-0,155; p=<0,05). Ada hubungan positif dan signifikan antara task approach skills aspek standar dan nilai kinerja dengan dependent career decision making (r=0,200; p=<0,01), proses persepsi dan kognitif dengan dependent career decision making (r=0,177; p=<0,05), set mental dengan dependent career decision making (r=0,215; p=<0,01), dan respon emosional dengan dependent career decision making (r=0,173; p=<0,05). Dapat disimpulkan hubungan paling erat ditunjukkan oleh task-approach skills aspek set mental dengan dependent career decision making. Berdasarkan hasil tersebut maka disarankan guru BK dapat memberikan pelayanan bidang karir secara sistematis dan berkesinambungan dimulai dari kelas X, lalu kelas XI, dan XII. Abstract The purpose of the research is to knowing and analyzing the relationship between aspects of task-approach skills with aspects of career decision making. This research used quantitative method with correlational approach. The samples were 142 out of 240 students taken by simple random sampling. The data analysis used descriptive quantitative analysis and hypothesis test with Person Product Moment correlation. The result of the descriptive analysis showed that the task-approach skills and the career decision making were included in the medium category. The result of the inferential statistical analysis showed that there was positive and significant correlation between the standard aspects of task-approach skills with performance value of career decision making (r=0,145; p=<0,05). There was negative correlation between the perception and cognitive process aspect of task-approach skills with impulsive career decision making (r=-0,155; p=<0,05). There was positive and significant correlation between standard aspect of task-approach skills with performance value of career decision making (r=0,200; p=<0,01), perception and cognitive process of dependent career decision making (r=0,177; p=<0,05), mental set with dependent career decision making (r=0,215; p=<0,01), emotional responses with dependent career decision making(r=0,173; p=<0,05). It can be concluded that the closest relation shown by mental set aspect of task-approach skills with dependent career decision making. Based on the result above, it is suggested to the BK teacher to provide a systematic and continuous career counseling services started from grade X, XI, and XII.